PENGEMBANGAN MEDIA PEMBELAJARAN TANGGA PINTAR PADA MATERI PENJUMLAHAN DAN PENGURANGAN SISWA KELAS 2 DI SD NEGERI KESONGO II - Wahyuni, Diah Ayu Sri; Raharja, Hawwin Fitra; Dwi Rochmania, Desty (IJPSE Indonesian Journal of Primary Science Education, 2024)
This research is a type of development research using the ADDIE model which includes Analysis, Design, Development, Implementation, Evaluation. This model is used to solve problems in learning addition and subtraction. The subjects of this research were grade 2 students at SD Negeri Kesongo II. Data analysis techniques using field notes, validator questionnaires and student response questionnaires. The validity of the smart ladder learning media is said to be valid with a percentage of 96.66%, as well as the validity of the material with a percentage of 97%. The process of implementing this learning media was carried out at SD Negeri Kesongo II, especially in class II. This implementation was carried out twice, namely on a small scale and a large scale. Small-scale trials were applied to 5 students by random selection, then large-scale trials were applied to all class II students. Thus, the implementation of the Smart Ladder learning media received a score of 96.5% with very good criteria applied to Mathematics learning. Therefore, it can be concluded that the smart ladder learning media can be well received and applied to addition and subtraction material.